Ultrasound-Guided Transversus Abdominis Plane Block versus Continuous Wound Infusion for Post-Caesarean Analgesia: A Randomized Trial - Chandon, Michel (Public Library of Science, 2014)
OBJECTIVE: To compare the analgesic effect of ultrasound-guided Transversus Abdominis Plane (TAP) block versus Continuous Wound Infusion (CWI) with levobupivacaine after caesarean delivery. METHODS: We recruited parturients undergoing elective caesareans for this multicenter study. Following written informed consent, they received a spinal anaesthetic without intrathecal morphine for their caesarean section. The postoperative analgesia was randomized to either a bilateral ultrasound guided TAP block (levobupivicaine = 150 mg) or a CWI through an elastomeric pump for 48 hours (levobupivacaine = 150 mg the first day and 12.5 mg/h thereafter). Every woman received regular analgesics along with oral morphine if required. The primary outcome was comparison of the 48-hour area under the curve (AUC) pain scores. Secondary outcomes included morphine consumption, adverse events, and persistent pain one month postoperatively. RESULTS: Recruitment of 120 women was planned but the study was prematurely terminated due to the occurrence of generalized seizures in one patient of the TAP group. By then, 36 patients with TAP and 29 with CWI had completed the study. AUC of pain at rest and during mobilization were not significantly different: 50 [22.5–80] in TAP versus 50 [27.5–130] in CWI (P = 0.4) and 190 [130–240] versus 160 [112.5–247.5] (P = 0.5), respectively. Morphine consumption (0 [0–20] mg in the TAP group and 10 [0–32.5] mg in the CWI group (P = 0.09)) and persistent pain at one month were similar in both groups (respectively 29.6% and 26.6% (P = 0.73)). CONCLUSION: In cases of morphine-free spinal anesthesia for cesarean delivery, no difference between TAP block and CWI for postoperative analgesia was suggested. TAP block may induce seizures in this specific context. Consequently, such a technique after a caesarean section cannot be recommended. TRIAL REGISTRATION: ClinicalTrials.gov NCT01151943